The waves of democratization theories and Arab regimes: between transitology and Arab exceptionalism - Tsatsanis, E. (Science and Society: Journal of Political and Moral Theory, 2012)
On occasion of the outbreak of a wave of popular mobilization in the Arab world (mainly) during the first half of 2011, the article examines the ways in which political science theories (and democratization theories in particular) have in the past analyzed and explained the relationship between Arab regimes and democracy: the potential for liberalization in the region, the factors that affect the intensification of demands for democracy and, finally, the mechanisms that facilitate the protracted survival of non-democratic forms of governance in the Arab world. The first part of the article offers a brief presentation of the ebb and flow of democratization theories, from the hypotheses of modernization theory to the contemporary 'transitology' paradigm. In the second part, the focus is transferred to the theoretical approaches that were developed mainly within the domain of Middle Eastern studies, often articulated as direct criticisms of the basic assumptions of democratization theories. The main aim of these approaches is to trace the causes that can account for the durability of Arab authoritarian regimes, while abandoning the assumption that Arab political systems are in a process of transition to democracy. The last section of the article offers an assessment of possible repercussions for democratization theory caused by the 2011 mobilizations.